RUMAH TAHFIDZ ANAK DI BANJARMASIN - Syifa, Muhammad; Dahliani, Dahliani (UNIVERSITAS LAMBUNG MANGKURAT, 2024)
The children's tahfidz house is a conscious effort to eradicate the phenomenon of Al-Qur'an illiteracy that occurs in society due to modernization that is currently occurring. In the tahfidz house learning process, problems that arise are related to ineffective and efficient learning methods due to limited space to accommodate tahfidz house activities and events. Children who study in a space that is not conducive will hamper their learning process and cause children to be distracted by conditions outside of learning. So that children's understanding in listening to the teacher's explanation will decrease and end up with children who cannot understand the lesson. The result of the design is a design concept related to tahfidz home learning methods by paying attention to the child's character through an architectural approach to make it easier for children to learn the Koran. The method adopted is to make children familiar with the learning material, as well as developing children's interests, skills, attitudes and behavior.